2017
DOI: 10.5901/jesr.2017.v7n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Parents of Children with Intellectual Disabilities in Croatia

Abstract: The goal of the present study was to examine the quality of life (QOL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
3
10
0
3
Order By: Relevance
“…This finding is in line with the results of the studies performed by Rassouli et al [50], showing that mothers' interaction with children having behavioral problems and special needs affects the quality of their lives and reduces their performance. Previous studies have also shown that caring for a disabled child affects the quality of life of mothers [51][52][53][54]. These findings were revealed to be in agreement with those of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in line with the results of the studies performed by Rassouli et al [50], showing that mothers' interaction with children having behavioral problems and special needs affects the quality of their lives and reduces their performance. Previous studies have also shown that caring for a disabled child affects the quality of life of mothers [51][52][53][54]. These findings were revealed to be in agreement with those of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study revealed that the level of education of mothers with disabled children affects their quality of life; thus, mothers with lower levels of education have a lower quality of life. The results of this study are in line with the studies of Klassen et al [62], Zareinejad et al [63], and Misura et al [54]. The results of the study of Gheysaranpour et al [60] on parents with a child with thalassemia showed that parents with higher education had a better quality of life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies performed with parents of infants with chronic diseases also suggest that other variables than infant-related factors influence the QoL of mothers and fathers, in particular factors related with characteristics of mothers and fathers and health care environment [41,48,49]. However, some of these factors were not tested by most of the studies included in this scoping review, namely those associated with parents' self-efficacy and coping strategies [41,50], maternal and paternal educational level [51] and employment status [52], family socioeconomic status [51], quality of the marital relation [40], parental health-related behaviours such as eating habits and exercise [49], use of community-based developmental resources (e.g. early intervention programs) [47] and regulation of parental leave [48].…”
Section: Current State Of Research and Future Directionmentioning
confidence: 97%
“…With the problem encountered by the parents of children with special educational needs, parental self-efficacy can be developed through parental training programmes (Hohlfeld et al, 2018). The support training programmes will create a quality of life for parents who have children with special educational needs (Misura & Memisevic, 2017).…”
Section: Discussionmentioning
confidence: 99%